A Survey of Studies of the Costs of Reducing Greenhouse Gas Emissions - Hoeller, Peter (OECD Economics Department Working Papers, 1990)
This paper surveys various estimates of the macroeconomic implications of reducing greenhouse gas emissions. Most available studies focus on policies to reduce CO2 emissions and are limited to the costs of such policies. The survey first examines the key factors shaping baseline emission scenarios. It then looks at the aggregate cost of emission reductions, as shown by both global and country-specific models, and discusses the key determinants of the model outcomes. The paper also briefly reviews other options for reducing greenhouse gas emissions and draws some more general lessons for the policy response to the threat of climate change ...